PENGARUH REBUSAN DAUN BINAHONG (ANREDERA CARDIFOLIA) TERHADAP KADAR GULA DARAH PADA LANSIA DM TIPE II DI PUSKESMAS KOTA DATAR - Flora Sijabat; Rinco Siregar; Marthalena Simamora (Universitas Pahlawan, 2022)
Diabetes mellitus (DM) is a metabolic disease that occurs due to damage to insulin secretion and insulin action which can be measured by looking at blood glucose levels. Binahong leaves contain saponins which have insulin-like activity, can inhibit lipolysis, and increase glucose uptake by adipose cells. This study aims to determine the effect of binahong leaf decoction on blood sugar levels in the elderly with type II diabetes mellitus at Kota Datar Public Health Center. Hamparan Perak Sub distict. This study is a quasi-experimental study with a pre and post test only one group design on 22 elderly people at Kota Datar Public Health Center, Hamparan Perak Sub Distict with binahong leaf decoction and the intervention is carried out for 14 days. The paired-test method is used to analyze the different tests for the effect of binahong leaf decoction on blood sugar levels in the elderly before and after the intervention. The results show that the average blood sugar level of the elderly with type II diabetes before being given binahong leaf decoction iss 182.41 mg / dl with an SD value of 31,304, and the lowest blood sugar level is 89 mg / dl and the highest is 201 mg / dl. The average of blood sugar level in the elderly with type II diabetes mellitus after being given binahong leaf decoction is 151.82 with SD value of 31.304, and the lowest blood sugar level is 89 mg / dl and the highest is 201 mg / dl. There is a significant difference in blood sugar levels in the elderly with type II diabetes mellitus at Kota Datar Public Health Center, Hamparan Perak Sub distict with P value = 0.001 (Î± <0.05). There is a decrease in blood sugar levels in the elderly with type II diabetes. It is Concluded that giving binahong leaf stew can reduce blood sugar levels in the elderly with type II diabetes mellitus at Kota Datar Community Health Center, Hamparan Perak Sub distict.